Comparative efficacy and safety of JAK inhibitors as monotherapy and in combination with methotrexate in patients with active rheumatoid arthritis: A systematic review and meta-analysis - Liu, Li; Yan, Yi-Dan; Shi, Fang-Hong; Lin, Hou-Wen; Gu, Zhi-Chun; Li, Jia (Frontiers in Immunology, 2022)
Background We aim to evaluate the efficacy and tolerability of Janus kinase inhibitors (JAKi) as monotherapy and in combination with methotrexate (MTX) in active rheumatoid arthritis (RA). Methods Medline, EMBASE, and Cochrane Library were systematically searched to identify relevant randomized controlled trials (RCTs). Pooled analysis was conducted using random-effects model, along with the risk difference (RD) and 95% confidence intervals (CIs). Results Three RCTs, including 2,290 patients, were included. JAKi (tofacitinib, baricitinib, and filgotinib) plus MTX displayed a higher proportion of patients meeting the American College of Rheumatology (ACR) criteria than JAKi alone at week 52 (ACR20 RD 0.032; 95% CI −0.027 to 0.091; ACR50 RD 0.050; 95% CI 0.003 to 0.097; ACR70 RD 0.056; 95% CI 0.012 to 0.100). Similar results were observed for ACR20/50/70 at week 24. No significant difference was found between two regimens for the proportion of patients achieving Health Assessment Questionnaire disability index improvement ≥ 0.22 at weeks 24 and 52. Regarding low disease activity and remission achievement, JAKi, in combination with MTX, contributed higher response rates than JAKi alone at weeks 24 and 52. Compared with JAKi monotherapy, combination therapy had a higher risks of treatment-emergent adverse events (TEAEs) and adverse events (AEs) leading to study discontinuation. Conclusion JAKi combined with MTX demonstrated superiority to JAKi monotherapy in terms of ACR responses, low disease activity and remission achievement. The two regimens presented comparable physical functioning measured by HAQ-DI improvement and similar tolerability, except for high risks of TEAEs and AEs leading to study discontinuation in combination therapy.